2020
DOI: 10.1021/acsnano.9b09125
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid–Polyphenol Hybrid Nanofilaments Mitigate Colitis and Regulate Gut Microbial Dysbiosis

Abstract: It is a desirable and powerful strategy to precisely fabricate functional soft matter through self-assembly of molecular building blocks across a range of length scales. Proteins, nucleic acids, and polyphenols are the self-assemblers ubiquitous in nature. Assembly of proteins into flexible biocolloids, amyloid fibrils with high aspect ratio, has emerged as an unchallenged templating strategy for high-end technological materials and bio-nanotechnologies. We demonstrate the ability of these fibrils to support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 75 publications
(126 reference statements)
2
79
0
Order By: Relevance
“…Hu et al constructed amyloid-polyphenol hybrid nanofilment hydrogels with higher EGCG loading capacity than other delivery systems (Fig. 9(a)) [50]. After oral administration, the hydrogel could enter the small intestine from the stomach, finally enter the large intestine and remain in the colon for a long time (Fig.…”
Section: Polyphenols-based Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al constructed amyloid-polyphenol hybrid nanofilment hydrogels with higher EGCG loading capacity than other delivery systems (Fig. 9(a)) [50]. After oral administration, the hydrogel could enter the small intestine from the stomach, finally enter the large intestine and remain in the colon for a long time (Fig.…”
Section: Polyphenols-based Npsmentioning
confidence: 99%
“…The mechanism of intimate interactions between redox-active NPs and gut microbiota is closely associated with ROS/RNS. Studies have brought evidence that NPs-mediated ROS/RNS scavenging can interfere with the respiration of pathogenic bacteria (Proteobacteria) induced by IBD, thereby reducing the relative abundance of pathogenic bacteria and restoring the homeostasis of gut microbiota [50]. However, some redoxactive NPs are known as ROS/RNS generators, and oxidative Figure 1 The relationship between IBD, ROS/RNS and gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Given the possibility to get tailored species, mostly in terms of surface functionalities, release capacity, and bio-compatibility, many have tried getting formulations capable of operating at the gut level [99], gene silencing [100], bone tissue regeneration [101][102][103], preparing devices [104] and/or decorating NPs with human stem cells [105], and anticancer therapy [106], as well. We do not know exactly how efficient the mentioned formulations are compared to canonical ones, but it expected that their safe use is close to be effective in vivo.…”
Section: Molecular Medicinementioning
confidence: 99%
“…The damage to intestinal mucosal barrier can cause the reduced secretion of immunoglobulins and impaired function of immune organs, thereby diminishing an immune response [2]. The gut microbiota, a complex community consisting of over 100 trillion bacteria in the distal gut, and their metabolites constitute the chemical and biological barriers of intestinal mucosa [3]. The previous report indicated that speci c bacterial phylotypes were parallel to the expression of tight junction proteins, but impaired intestinal mucosal barrier could induce bacterial translocation [4].…”
Section: Introductionmentioning
confidence: 99%